Pengaruh Kompensasi Terhadap Kinerja Karyawan Pada PT. Surya Pilar Perkasa Pekanbaru - Rofidah, Siti (Sekolah Tinggi Ilmu Ekonomi Riau, 2023)
The purpose of this study was to determine the effect of compensation on employee performance at PT. Surya Pilar Perkasa Pekanbaru. The population in this study were all employees of PT. Surya Pilar Perkasa Pekanbaru, totaling 89 people.Data analysis used simple linear regression method using validity test, reliability test, normality test, RÂ² and t test. The test was conducted to determine the relationship between the independent variable (independent variable) and the dependent variable (dependent variable).Based on the results of the research analysis, it was found that t count was greater than t table (10,846 > 1,988). Thus it can be concluded that the compensation variable (X) has an effect on employee performance. The simple regression results show Y = a + bX, namely: Y = 15.341 + 0.904 X. From the regression equation, it is concluded that the regression coefficient of bX is positive. This shows that if the independent variable is increased the equation will cause an increase in the dependent variable. The result of R Square of 0.558 explains that performance is influenced by compensation of 55.8%.